2015
DOI: 10.1007/s00595-015-1233-0
|View full text |Cite
|
Sign up to set email alerts
|

Is left upper lobectomy for lung cancer a risk factor for cerebral infarction?

Abstract: Cerebral infarction occurs at a high frequency in patients who undergo left upper lobectomy for lung cancer. Thrombosis in the left superior pulmonary-vein stump might cause cerebral infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 20 publications
5
72
2
Order By: Relevance
“…Yamamoto et al [1] reported no relationship between operative time and the risk of cerebral infarction. However, increased operative time indicates increased time in the lateral position, thereby increasing the risk of cerebral infarction.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Yamamoto et al [1] reported no relationship between operative time and the risk of cerebral infarction. However, increased operative time indicates increased time in the lateral position, thereby increasing the risk of cerebral infarction.…”
Section: Discussionmentioning
confidence: 98%
“…After lobectomy, the length of the left superior PV stump is longer than that of any other PV stump. Yamamoto et al [1] reported six cases of cerebral infarction out of 562 lobectomies for lung cancer, including five patients who underwent LUL. Hattori et al [6] reported 10 patients with cerebral infarction out of 1670 patients who underwent lobectomy or more intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVT may be a much more common complication after LUL than previously assumed; however, an effective method of preventing it has yet to be established. Thromboembolic events associated with PVT can be life-threatening, and a retrospective study found that the rate of cerebral infarction was extremely high, especially after LUL (3,17). Thromboembolic events have deleterious effects on the outcome after surgery (18).…”
Section: Discussionmentioning
confidence: 99%
“…There are several recent reports that left upper lobe (LUL) lobectomy is a risk factor for the development of postoperative cerebral thromboembolism [1,2,3]. The mechanism of cerebral infarction after LUL lobectomy may include stasis of blood flow in the stump of the left upper pulmonary vein because the left upper pulmonary vein stump may be longer than other pulmonary vein remnants for anatomical reasons [2].…”
Section: Introductionmentioning
confidence: 99%